Rural development - Pain, Adam; Hansen, Kjell (Routledge, 2019)
Rural Development is a textbook that critically examines economic, social and cultural aspects of rural development efforts both in the global north and in the global south. By consistently using examples from the north and the south the book highlights similarities of processes as well as differences in contexts.